2014
DOI: 10.1016/j.ijsu.2014.07.264
|View full text |Cite
|
Sign up to set email alerts
|

Management of intrahepatic stones: The role of subcutaneous hepaticojejunal access loop. A prospective cohort study

Abstract: The subcutaneous access loop offers the advantage of permanent access for the successful management of retained or re-formed intrahepatic stones with minimal morbidity since it permitted easy access to intrahepatic ducts using the conventional forward-viewing endoscope or the choledochoscope, without the additional morbidity of a biliary-cutaneous fistula or transhepatic access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Moreover, disease progression occurs in most patients even after adequate treatment. 10 Surgery is strongly considered for relatively young patients with liver abscess and suggested biliary stricture like case 2. Surgical treatment is traditionally the standard of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, disease progression occurs in most patients even after adequate treatment. 10 Surgery is strongly considered for relatively young patients with liver abscess and suggested biliary stricture like case 2. Surgical treatment is traditionally the standard of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Success rates of the above treatments range from 72% to 92%. 10 Percutaneous transhepatic cholangioscopic lithotomy or lithotriopsy is nowadays commonly used for the removal of IHD stone or difficult cases of CBD stone. 11 Transpapillary endoscopic treatment with ultraslim endoscopy can be another option to access the IHD to remove the stone.…”
Section: Discussionmentioning
confidence: 99%
“…A single surgical procedure and avoiding repeated manipulation of biliary tract is necessary to achieve optimal outcome. The atrophied liver should be resected and the bile duct explored to avoid residual stone 5 , 7 , 9 , 16 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The left liver lobe is often the most frequent location of hepatolithiasis. 20 The acute angle taken by the left hepatic duct when it reaches the confluence resulting in biliary stasis, especially in the background of biliary stenosis. Some studies have shown a higher frequency of right side involvement, especially in the posterior segments of postcholecystectomy patients.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Due to the expected need for long term access to the intrahepatic biliary ducts, procedures such as hepaticocutaneous jejunostomy with subcutaneous access loop, were favoured subsequently. 20 In case of large calculi (especially in the left lobe), hepatic atrophy, abscesses, suspected cholangiocarcinoma or failure of other therapeutic modes, surgical resection may be considered appropriate.…”
Section: Surgical Managementmentioning
confidence: 99%